Decreased Collagen and Increased Matrix Metalloproteinase-13 in Experimental Abdominal Aortic Aneurysms in Males Compared with Females - Cho, Brenda S (2009)
BACKGROUND: This study examined gender differences in collagen regulation during rodent experimental abdominal aortic aneurysm (AAA) formation. METHODS: Infrarenal aortas of male and female rats were perfused with elastase or saline (control). Aortic diameters were measured at baseline (day 0), and on post-operative days 7 and 14. TGF-β1, collagen subtypes I and III, and MMP-13 (collagenase) expression and/or protein levels from aortic tissue were determined by RT-PCR and Western Blotting. Aortic tissue was stained for total collagen, neutrophils, and macrophages using immunohistochemistry on days 4 and 7. RESULTS: Seven and 14 days following perfusion, aortic diameter increased significantly in elastase-perfused males compared with females (P<0.001 for each). Four and 7 days post-perfusion, significantly more neutrophils and macrophages were present in elastase-perfused males compared with females. Seven days post-perfusion, protein levels of TGF-β1 were lower in males compared with females (P=0.04). Type I collagen levels also decreased on days 7 (P<0.001) and 14 (P=0.002), and type III collagen levels decreased on days 7 (P<0.001) and 14 (P<0.001), in males compared with females. By Masson's Trichrome, less adventitial collagen was present in the elastase-perfused males compared with females. MMP-13 expression (P<0.001) and protein levels (P=0.006) in elastase-perfused males were higher than females on day 14. CONCLUSIONS: This study documents a decrease in types I and III collagen with a concurrent increase in MMP-13 following elastase perfusion in males compared with females. These data suggest that alterations in extracellular matrix collagen turnover may be responsible for altered AAA formation between genders.